2004
DOI: 10.1093/ije/dyh020
|View full text |Cite
|
Sign up to set email alerts
|

Height, predictors of C-peptide and cancer risk in men

Abstract: Maximal growth in the pre-adult period and hyperinsulinaemia during adulthood may largely underlie the excess risk of some cancers that are common in Western populations. A substantial proportion of these cancers may be modifiable in adulthood, through alterations in body weight, sedentary behaviour, and dietary patterns that stimulate hyperinsulinaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 65 publications
4
38
0
Order By: Relevance
“…Of 18 prospective cohort studies published to date, 11 showed no association (34,35,41,(44)(45)(46)(47)(48)(49)(50)(51) and 7 showed statistically significant elevations in risk with increasing height (27)(28)(29)(30)(31)(32)(33). Risk increases in the latter studies varied from 20% to 80% for men in the highest versus the lowest quantile of height.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Of 18 prospective cohort studies published to date, 11 showed no association (34,35,41,(44)(45)(46)(47)(48)(49)(50)(51) and 7 showed statistically significant elevations in risk with increasing height (27)(28)(29)(30)(31)(32)(33). Risk increases in the latter studies varied from 20% to 80% for men in the highest versus the lowest quantile of height.…”
Section: Discussionmentioning
confidence: 98%
“…This homogeneity also adds strength to the study, however, in that differences in height may be influenced to a proportionally greater degree by variations in environmental exposures (particularly nutrition), as compared with heredity and socioeconomic factors (41). In fact, five of the seven prospective studies that yielded positive associations between height and prostate cancer risk were conducted in cohorts that were relatively homogeneous with respect to ethnicity alone (28) or both ethnicity and social class (27,29,30,32). An additional minor limitation is that measured height may not have reflected maximal adult height in our study population because taller men tended to be younger, and it is known that standing height decreases with advancing age (42).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial studies done in prostate cancer showed a correlation with plasma IGF-1 levels (Chan et al, 1998). Subsequently, various studies have confi rmed high levels of IGF-1 and insulin levels associated with prostate cancer risk prospectively (Harman et al, 2000;Kaaks et al, 2003;Giovannucci et al, 2004). A link between breast cancer risk and hyperinsulinemia (measured by fasting C-peptide levels) has been shown mainly in postmenopausal breast cancer (Verheus et al, 2006).…”
Section: Insulin Like Growth Factor and Cancermentioning
confidence: 99%
“…Attained adult height can thus be used as a biomarker for early childhood energy intake (Albanes et al, 1988). There is some indication for a positive association between adult height and overall risk of malignancy (Batty et al, 2006), although the data reported are inconsistent as yet (Giovannucci et al, 2004).…”
mentioning
confidence: 99%